Dåajmijes vuekie: A Sami Aesthetic Paradigm - Kappfjell, Lena; Gaski, Harald; DuBois, Thomas A. (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2024)
The South Sámi concept of dåajmijes vuekie is used to discuss a nuanced system of evaluative norms operating in Sámi culture, past and present, in relation to objects, behavior, and activities. Where Western aesthetics may focus on surface appearance, dåajmijes vuekie emphasizes effective action in relation to practical needs, social interaction, and ethics. The authors suggest that evaluative norms associated with Sámi traditional knowledge and activities can provide valuable insights for understanding not only Sámi traditional life but also works of contemporary Sámi artists and writers who draw on Sámi cultural norms in conscious ways.